The association between physical fitness parameters and in-season injury among adult male rugby players: a systematic review - MacMillan C.; Olivier B.; Benjamin-Damons N.; MacMillan G. (The Journal of Sports Medicine and Physical Fitness, 2022)
INTRODUCTION: The high prevalence of injury among rugby players emphasizes the need for research related to injury risk factors. Physical fitness-related risk factors are likely culprits contributing to both contact and non-contact injuries. Establishing associations between preseason measured physical fitness aspects and injury risk, not only provide players` baseline fitness parameters but could also identify injury prone players, thereby contributing to injury prevention strategies. Therefore, the objective of this review was to assess and summarize scientific literature related to the association between preseason measured physical fitness tests and in-season injury among male rugby players. EVIDENCE ACQUISITION: A systematic review was performed in compliance with the PRISMA 2020 Guidelines. This review considered observational, prospective cohort study designs. Studies that included male rugby (rugby union, rugby league, Australian football rules and rugby sevens) players aged 18 years or above from all levels of participation, evaluating the association between physical fitness test outcome and injury, were considered for inclusion. The three-step search strategy aimed at finding both published and unpublished studies in any language. Searched databases included Medline via PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Physiotherapy Evidence Database (PEDro), the Cochrane Controlled Trials Register in the Cochrane Library, ProQuest 5000 International, ProQuest Health and Medical Complete, EBSCO MegaFile Premier, SPORTDiscus with Full Text, SCOPUS and Science Direct. Key words used were "rugby," "injury," "physical fitness," and "risk factors." Papers that met the inclusion criteria were assessed by two independent reviewers for methodological validity prior to inclusion in the review using standardized critical appraisal tool for cohort studies from the Joanna Briggs Institute (JBI SUMARI). EVIDENCE SYNTHESIS: A total of 16 studies were eligible for inclusion in this review. The mean critical appraisal score was 82.63% (SD=17.86). Forty-meter sprint speed was associated with injury in all three (100%) studies that included the test. Inconsistencies in the statistical analysis, however, make comparison difficult. None of the studies that investigated upper (N.=1) and/or lower body power (N.=3) identified power as a risk factor. Conflicting results were found for the association between strength, flexibility, cardiorespiratory fitness, and injury. CONCLUSIONS: Identifying factors associated with injury risk is an important step in the injury prevention paradigm. Once identified, players can be screened for risk factors prior to participation in sport. Interventions, based on screening results, which not only improve performance but also decrease players` risk of sustaining injuries (i.e., physical fitness related risk factors), provide additional incentive for compliance. Overall, this review highlights the inconsistency in testing methods used to gauge specific physical fitness constructs among rugby players, limiting the extent to which comparison of results and pooling of data is possible.